Religious conversion: historical aspects and modern perspective - Weber, Edmund (Journal of religious culture, 2008)
Religious conversion has become a dangerous social and individual problem. In Latin America, a traditional Catholic area, Protestant sects are successfully con-verting more and more Catholics into their own communities. Therefore the Pope demands a strict control of these activities. In India e.g., the Catholic hierarchy is critizising the Indian governments which have forbidden conversion on non-spiritual reasons. Hindu organizations have started even very successfully to re-convert Indian Christians particularly of Dalit and tribal background. Buddhists are very successful in indirect and even direct conversion of many Westerners. Wah-habit missionaries spread their Neo-Islam in the Muslim societies and get more and more even non-Muslim converts. We should add the forcible and sometimes ex-tremely cruel conversions the atheistic states had executed since the last century. ...